Pricing Advices - Suehyun Kwon (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper studies a selling mechanism where the seller first charges a fee for advice (information structure) then sells a product. When the buyer has no private information, the seller can extract full surplus, both when the seller has private information and when he doesn't. If only the buyer has private information, the seller cannot extract full surplus. When both the seller and the buyer have private information, selling advice can strictly increase the probability of trade, and it is welfare-improving for both parties. In the private-value setting, Myerson-Satterthwaite no-trade theorem can be overcome by this mechanism. If the seller's valuation doesn't depend on the buyer type, then commitment power doesn't change results, but with interdependent values, the limited-commitment solution cannot replicate the full-commitment solution.
Keywords: 330; information design; dynamic informed-principal problem; interdependent values; limited commitment; Myerson-Satterthwaite